Impact of King III: The relationship between corporate governance mechanisms and listing suspensions - Mudimba, Gibson (College of Accounting, 2022)
In this study, the main focus was to investigate the relationship between listing suspensions and corporate governance mechanisms which are related to the board of directors. The study also examined the effectiveness of King III in improving corporate governance on companies listed on the Johannesburg Securities Exchange of South Africa (JSE). The matched pairs research design was utilised where a comparison of 56 suspended companies were selected for the study. The period covered by the study was 2006 to 2017. Control companies were selected to match all the relevant suspended companies. The matching was done in terms of time, industry and size (measured by total assets). The control company should not have been suspended in the year under consideration. With the use of the conditional logistic regression model to analyse the data, the study found that the practice of board performance evaluation significantly reduced the odds of suspension. Another key finding of the study was that the number of directors with shares in the company has a statistically significant negative correlation to the odds of suspension. A comparison of King II and King III regimes indicates a stronger corporate governance era during the King III phase. Board size, the proportion of non-executive directors, and the number of independent directors and board performance evaluations increased significantly during the King III phase. Additionally, the study notices a decrease in the number of JSE listing suspensions during the King III era as compared to King II which implies that King III brought in stronger governance measures to listed companies in South Africa. Corporate governance is a critical focal point in managing corporates, raising capital as well as performing valuations of entities. The governance aspects relating to the actions of directors appear to have a direct correlation in determining whether a company will be suspended or not from the JSE. Findings of the study have contributed to the body of literature in proving the presence of a correlation between corporate failure and the failure of corporate governance structures. The findings in this study have a significant impact on policymakers in South Africa as they continue to strengthen corporate governance.